AnÃlise descritiva dos autos de infraÃÃes lavrados nas fiscalizaÃÃes das empresas do Simples Nacional no Estado do CearÃ durante os exercÃcios de 2010 e 2011 - Fernando JosÃ Ferreira Pimentel (2012)
CearÃ Finance Department has developed over the years *checking ways* through a large amount of companies, ICMS taxpayers. It concerns with report fraud waste and abuse systematically relating to ICMS program and operations in diverse economic areas issued by small, medium and large companies. The reports are carried out year by year. In that occasion many companies are selected through adoption of technical criteria which are inspected by CATRI â Tax Administration Coordination. This paper intends to lay down many results achieved by SEFAZ through inspections performed at companies which adopted the *SIMPLES NACIONAL* regarding the years 2010 and 2011. The reports are considering the years 2007-2011. With descriptive statistics at disposal we aim to identify important factors that serve to reflect on how these companies are behaving just after implementing the *SIMPLES NACIONAL*. Regardless to say that public policies are decisive to the small and medium entrepreneurs as well as for increasing the social welfare. However, the Government should pay attention to the monitoring of its own work in order to prevent tax evasion or fraud waste which continue still to exist. The lesson from this paper is the following: companies inspected and which adopted the *SIMPLES NACIONAL*, while enjoying a lower tax burden, committed several types tax law abuses. They eliminate taxes that were due to Ceara State.